2019
DOI: 10.1111/jsap.12990
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic findings in cats with aspiration pneumonia: retrospective evaluation of 28 cases

Abstract: Objectives To describe the clinical syndrome of aspiration pneumonia in cats and record potential predisposing factors. Materials and Methods A retrospective medical records search for cats with a diagnosis of “aspiration pneumonia” or “bronchopneumonia” was performed. Cases were included if they had a complete medical record and three‐view thoracic radiographs with pulmonary changes consistent with aspiration pneumonia and no other radiographic or physical examination findings suggestive of another cause of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…Hypoalbuminemia could be suggestive of lung inflammation and vasculitis that resulted in leakage of albumin into the alveolar space (Kogan et al, 2008). The radiographic views of cases suffering from pneumonia and aspiration pneumonia revealed a predominantly interstitial pattern and alveolar infiltrate, some cases showing lung consolidation, the same results were previously recorded by Dear (2014) and Levy et al (2019). The radiographic views of dogs' chest suffering from kennel cough revealed a predominantly bronchial pattern, but some cases showed mixed pattern, the same result was previously recorded by Vindenes et al (2015).…”
Section: Discussionsupporting
confidence: 73%
“…Hypoalbuminemia could be suggestive of lung inflammation and vasculitis that resulted in leakage of albumin into the alveolar space (Kogan et al, 2008). The radiographic views of cases suffering from pneumonia and aspiration pneumonia revealed a predominantly interstitial pattern and alveolar infiltrate, some cases showing lung consolidation, the same results were previously recorded by Dear (2014) and Levy et al (2019). The radiographic views of dogs' chest suffering from kennel cough revealed a predominantly bronchial pattern, but some cases showed mixed pattern, the same result was previously recorded by Vindenes et al (2015).…”
Section: Discussionsupporting
confidence: 73%
“…Clinical signs and radiographic [36][37][38] findings (eg, right middle lobar consolidation or collapse) can also be considered suggestive of inflammatory airway disease rather than pneumonia. 16 As disease worsens, cats can become tachypneic with short, shallow breaths and nasal flaring. 17 Rarely do cat owners notice exercise intolerance associated with bacterial pneumonia.…”
Section: Clinical Signsmentioning
confidence: 99%
“…Fever is detected in 16% to 50% of cases, so it is not a reliable indicator of disease. 8,16,[18][19][20]…”
Section: Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the animals in this study, the alveolar pattern was observed. In the other, the mixed pattern (interstitial and alveolar) suggested a picture of bacterial pneumonia as described by Levy et al [19].…”
Section: Discussionmentioning
confidence: 79%